Ben - Giben dan Nase' Lanceng Pernikahan di Daleman Galis Bangkalan Madura Perspektif Hukum Islam - Syafi’ie , Moh. Toyyib (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2013)
This is a field research to answer the two fundamental questions, namely: what the status of the ben-giben and nase’ lanceng tradition related to marital contract in village Daleman, district Galis, region Bangkalan-Madura is, and how the point of view of the Islamic law to their legal status is. The data of the research are gained through interview to some of the village’s local religious figures and the participants of the ben-giben and nase’ lanceng. The collected data are then qualitatively analyzed by using a descriptive technique and inductive-deductive mindset. The study concludes that: first, the handing of the ben-giben and nase’ lanceng is that if the parents want to marry their child, they have to include the items required in the form of cattle, samper lasem, a basket of egg and a cone; second, the tradition of ben-giben and nase’ lanceng is not contrary to Islamic law and to the principle of marriage, namely the principle of willingness between the groom and the bride. Based on the above conclusions, the author recommends that such tradition may be continued and preserved to the next generation of the village. In addition, a belief about a negative impact of the tradition for the natives is necessarily clarified by the local religious figures since it is naturally happening under the God’s will.